Coefficient of Variation of Coarsely Sampled Heart Rate is Associated With Early Vasopressor Independence in Severe Sepsis and Septic Shock. (October 2015) - Brown, Samuel M.; Tate, M. Quinn; Jones, Jason P.; Kuttler, Kathryn G.; Lanspa, Michael J.; Rondina, Matthew T.; Grissom, Colin K.; Mathews, V. J.
Purpose: To determine whether variability of coarsely sampled heart rate and blood pressure early in the course of severe sepsis and septic shock predicts successful resuscitation, defined as vasopressor independence at 24 hours after admission. Methods: In an observational study of patients admitted with severe sepsis or septic shock from 2009 to 2011 to either of 2 intensive care units (ICUs) at a tertiary-care hospital, in whom blood pressure was measured via an arterial catheter, we sampled heart rate and blood pressure every 30 seconds over the first 6 hours of ICU admission and calculated the coefficient of variability of those measurements. Primary outcome was vasopressor independence at 24 hours; and secondary outcome was 28-day mortality. Results: We studied 165 patients, of which 97 (59%) achieved vasopressor independence at 24 hours. Overall, 28-day mortality was 15%. Significant predictors of vasopressor independence at 24 hours included the coefficient of variation of heart rate, age, Acute Physiology and Chronic Health Evaluation II, the number of increases in vasopressor dose, mean vasopressin dose, mean blood pressure, and time–pressure integral of mean blood pressure less than 60 mm Hg. Lower sampling frequencies (up to once every 5 minutes) did not affect the findings. Conclusions: Increased variability of coarsely sampled heart rate was associated with vasopressor independence at 24 hours after controlling for possible confounders. Sampling frequencies of once in 5 minutes may be similar to once in 30 seconds.